Female offenders: critical perspectives and effective interventions - Zaplin, Ruth T. (Jones and Bartlett Publishers)
An overview of delinquent girls : how theory and practice have failed and the need for innovative changes / Joanne Belknap and Kristi Holsinger -- The nature of female offending : patterns and explanation / Jennifer Schwartz and Darrell Steffensmeier -- Female offenders : a systems perspective / Ruth T. Zaplin -- Social treatment : a multiphased event / Frank B. W. Hawkinshire -- The relational theory of women's psychological development : implications for the criminal justice system / Stephanie S. Covington -- Power-belief theory : female criminality and the dynamics of oppression / Joyce Dougherty -- Explanatory diversity among female delinquents : examining taxonomic heterogeneity / Tim Brennan -- The treatment of female offenders : individual psychotherapy in systems-theory perspective / Bernard Weitzman -- Pre-adjudicated and adjudicated girls' reports on their lives before and during detention and incarceration / Joanne Belknap and Bonnie Cady -- Institutional assessment and classification of female offenders : from robust beauty to person-centered assessment / Tim Brennan -- Mental health issues, treatment, and the female offender / Susan Baugh, Susan Bull, and Kathy Cohen -- Female offenders and childhood maltreatment : understanding the connections / Joyce Dougherty -- Surviving violence : women's strength through connection / Carolyn Swift -- Needs assessment and treatment goal planning / Lorry Bradley -- Meditation, emotions, and female offenders / Elaine J. Yuen -- Preparing federal female offenders for reentry : shifting the paradigm to a skills-based model / John M. Vanyur, Nicole English, and Melinda Clark -- Programs that work : mothers / Ruth T. Zaplin and Joyce Dougherty -- Self-taught empowerment and pride : a multimodal/dual empowerment approach to confronting the problems of African American female offenders / Zelma Weston Henriques and Dolores Jones-Brown -- College mentoring program for incarcerated girls / Kristi Holsinger -- Evaluation of programs for female offenders / Kathleen Kendall -- Applying strategic management techniques to female offender programs and organizations / Rob Cimperman -- The "good hands" society : the application of insurance principles to uncivil actors and societal systems / David Zlowe -- Looking toward the future : the female offender as customer / Ruth T. Zaplin